Cardiovascular Risk Predictors High Sensitivity C-Reactive Protein and Plasminogen Activator Inhibitor-1 in Women with Lean Phenotype of Polycystic Ovarian Syndrome: A Prospective Case-Control Study - Shah, Ashok K.; Yadav, Birendra K.; Shah, Amrendra K.; Suri, Arpita; Deo, Saurabh K. (Journal of Laboratory Physicians, 2022)
Objective Accumulating evidence suggests increased cardiovascular risk in women with polycystic ovarian syndrome (PCOS) due to a cluster of factors, such as obesity, lipid abnormalities, impaired glucose tolerance (IGT), and hypertension. Markers such as high-sensitivity C-reactive protein (hs-CRP) and plasminogen activator inhibitor-1 (PAI-1) can provide an adjunctive method for the assessment of cardiovascular risk and can indicate future coronary heart diseases in women with lean PCOS.Materials and Methods In this prospective case-control study, women clinically diagnosed with PCOS (n = 25) with normal body mass index (BMI) and age and BMI-matched healthy controls (n = 75) were enrolled. The quantitative data were expressed as mean ± standard deviation (SD). Unpaired Student's t-test was used to compare the values (PCOS vs. controls) and Pearson's correlation coefficient was used to elucidate the relationship between the variables.Results The mean level of fasting blood sugar, serum total cholesterol, low-density lipoprotein (LDL), thyroid-stimulating hormone (TSH), follicle-stimulating hormone (FSH), luteinizing hormone (LH), prolactin (PRL), hs-CRP, and PAI-1 were significantly increased in PCOS patients (p < 0.000) compared with the control patients. Of the reported cases, 54.16% had hs-CRP levels greater than 3 mg/L. When the cases were further divided into normal (n = 20) and IGT (n = 5), hs-CRP values were significantly higher in IGT group as compared with normal glucose tolerance (NGT) group. On bivariate correlation analysis, hs-CRP had significant correlations with PAI-1 (r = 0.41, p < 0.000), waist-to-hip ratio (WHR; r = 0.23, p = 0.02), fasting blood sugar (FBS; r = 0.26, p = 0.009), LDL (r = 0.20, p = 0.03), TSH (r = 0.42, p < 0.000), and LH-to-FSH ratio (r = 0.24, p = 0.01).Conclusion Women with lean phenotype of PCOS suffer from many metabolic abnormalities such as abdominal obesity, dyslipidemia, hyperandrogenemia, and insulin resistance. The findings of the study suggest that environment of ongoing low-grade inflammation due to infiltration further exacerbates the metabolic derangements and cardiovascular risk. The investigations as hs-CRP and PAI-1 will help in early identification, diagnosis, and management of cardiovascular diseases associated with lean type of PCOS. These markers can prove to be beneficial in monitoring any unfavorable changes in cardiometabolic profile of such patients.
Keywords: cardiovascular disease; hs-CRP; lean phenotype of PCOS; PAI-1